Drying of Functional Hydrogels: Development of a Workflow for Bioreactor-Integrated Freeze-Drying of Protein-Coated Alginate Microcarriers for iPS Cell-Based Screenings - Johnn Majd Balsters; Alexander Bäumchen; Michael Roland; Stefan Diebels; Julia C. Neubauer; Michael M. Gepp; Heiko Zimmermann (Gels, 2025)
Protein-coated ultra-high viscosity (UHV)-alginate hydrogels are essential to mimic the physiological in vivo environment of humans in several in vitro applications. This work presents an optimized bioreactor-integrated freeze-drying process for MatrigelTM-coated UHV-alginate microcarriers in the context of human induced pluripotent stem cell (hiPSC) expansion. The impact of freeze-drying on the UHV-alginate microcarriers using trehalose 100 mg/mL in 0.9% NaCl as a lyoprotective agent, as well as the stem cell response using hiPSCs, was analyzed using microscopy-based screenings. First observations of the process showed that the integrity of the cake was preserved in the samples with a maximum vapor exchanging rate. Following rehydration, the UHV-alginate microcarriers retained their original morphology. Upon the addition of Poloxamer 188, stickiness and bubble formation were reduced. The expansion of hiPSCs in a suspension bioreactor resulted in a 5–7-fold increase in total cell count, yielding at least 1.3 × 107 cells with viability exceeding 80% after seven days of cultivation. In flow cytometry analysis, the pluripotency factors OCT3/4 and SSEA4 resulted in positive signals in over 98% of cells, while the differentiation factor SSEA1 was positive in fewer than 10% of cells. Supported by preceding in silico predictions of drying time, this study presents, for the first time, basic steps toward a “ready-to-use” bioreactor-integrated freeze-drying process for UHV-alginate microcarriers in the iPSC context.